The Role of IL-17-Mediated Inflammatory Processes in the Pathogenesis of Intervertebral Disc Degeneration and Herniation: A Comprehensive Review - Suyama, Kaori; Sakai, Daisuke; Watanabe, Masahiko (Frontiers in Cell and Developmental Biology, 2022)
It has been reported that degenerated and herniated lumbar intervertebral discs show high expression of IL-17, suggesting that local immune reactions occur in patients with low back pain. While clinical sample analyses from different laboratories confirm this, it is not deeply not known on how IL-17 is induced in the pathology and their interactions with other inflammatory responses. This conscience review organizes current laboratory findings on this topic and present trajectory for full understanding on the role of IL-17 in pathology of intervertebral disc disease.